Reconstruction of late 19th century geometry of Kotárjökull and Breiðamerkurjökull in SE-Iceland and comparison with the present - Snævarr Guðmundsson 1963- (2014)
Glaciers in Iceland have retreated notably since the end of the 19th century in response to climate warming. Prior to that glaciers advanced during the Little Ice Age (LIA), which lasted several centuries. The recession has had many geomorphological and hydrological effects, for example a widespread exposure of moraines and other glacial landforms, changes in river courses and crustal uplift. This thesis contributes to studies of the glacier changes with two papers. They focus on methods to construct digital elevation models (DEMs) of the outlet glaciers Kotárjökull and Breiðamerkurjökull in Öræfajökull and Vatnajökull, SE-Iceland, at the end of the LIA ~1890 as well as Breiðamerkurjökull in 1945. The DEMs are derived several data sources including topographic maps, aerial photographs, oblique photography, remote sensing, field tracing of geomorphological features and a LiDAR DEM from 2010. Comparison of the derived ice surface elevation in ~1890 and 1945 with the 2010 DEM provides a quantitative estimate of past glacier changes since the LIA maximum. The high precision LiDAR DEM enables the correction of the topographical maps from 1904 and 1945 and the extraction of ground control points to interpret old photographs in terms of elevation changes until 2010. The changes in the glacier elevation are greatest at the termini, up to 180 m for Kotárjökull and >200 m for Breiðamerkurjökull, but decrease to near zero in the uppermost part of the accumulation area. Breiðamerkurjökull (10–1760 m a.s.l.) has retreated about 5 km since ~1890, exposing 114 km2 of proglacial terrain and lost a volume of ~69 km3 water equivalent (w.e.); corresponding to an average specific annual mass loss of 0.64 m w.e./yr. Kotárjökull (350–1800 m a.s.l.) retreated 1.3–2 km in the same time period, lost 2.7 km2 of its ~1890 area and and 0.4 km3 w.e. or 30% of its volume, corresponding to a specific mass loss rate of 0.23 m w.e./yr. The results are an encouragement to continue with estimation of other glaciers and ice caps at the end of ...